LEAD IDENTIFICATION BASED ON SEISMIK 2D DATA, NORTH KABAENA SUB-BASIN, BONE BASIN, SOUTHERN SULAWESI - Darwansyah, Fiqry; Sunardi, Edy; Ilmi, Nisa Nurul; Ginting, Agus Santa (Journal of Geological Sciences and Applied Geology, 2018)
The research was conduct in north Kabaena sub – basin in the middle of the Bone Bay and it is the result of tectonic development of Sulawesi since the early Miocene. Since early Miocene tectonic development creating spaces for the accommodation process of sedimentation in Bone Bay. The existence of a process of sedimentation in the Bone Bay allows the existence of oil and gas. As a contribution to the development of science and oil & gas industry in Indonesia, study of the north Kabaena sub – basin was conducted with seismic 2D and gravity anomalies. This study is aiming to find out potential area through the subsurface contour maps. This research start with the analysis of the fault on the 2D seismic interpretation and aided by gravity anomaly data, followed by horizon interpretation using tectonostratigraphy approach as a marker. Both interpretation is a material to make subsurface contour maps. Through this research, we identified 5 packs of rocks from old to young is unit X, unit A, unit B, and unit C&D, and we proposed a lead's which is at unit C with carbonate build up type.